The Promise of Bacteriophage Therapy for Burkholderia cepacia Complex Respiratory Infections - Semler, Diana D.; Lynch, Karlene H.; Dennis, Jonathan J. (Frontiers in Cellular and Infection Microbiology, 2012)
In recent times, increased attention has been given to evaluating the efficacy of phage therapy, especially in scenarios where the bacterial infectious agent of interest is highly antibiotic resistant. In this regard, phage therapy is especially applicable to infections caused by the Burkholderia cepacia complex (BCC) since members of the BCC are antibiotic pan-resistant. Current studies in BCC phage therapy are unique from many other avenues of phage therapy research in that the research is not only comprised of phage isolation, in vitro phage characterization and in vivo infection model efficacy, but also adapting aerosol drug delivery techniques to aerosol phage formulation delivery and storage.